Process evaluation of temporary exemption implementation for emergency cases in St. Augustine Muheza designated district hospital - Msabaha, Rasmo (Mzumbe University, 2026)
A dissertation Submitted to School of Public Administration and Management of Mzumbe University in partial fulfillment of Requirements for the Award of Masters of Science Degree in Health Monitoring and Evaluation of Mzumbe University.